Colonial workers, imperial migrants and surveillance: policing in Le Havre, 1914–40. (2nd January 2018) - Marsh, Kate
ABSTRACT: This article explores how the police and municipal authorities of Le Havre responded to the colonial others who passed through, or resided in, the Seine-Inférieure port between the outbreak of the First World War and the defeat of France in 1940. Interrogating how the police and urban authorities monitored migrants to the port, it reveals how Le Havre's imperial and transnational space was distinctive in terms of the peoples who established themselves in the port, the ways in which they forged links with other peripheral locations throughout the French empire, and how the local authorities attempted to control migrants and incomers from the French overseas empire. It highlights particularities of Le Havre's urban space – notably its lack of a university and prestigious lycées, its pre-1914 history of militant strike action, its role as France's main transatlantic port, and the presence of a small colonial population with a narrow social-economic profile – and shows how these particularities resulted in the enactment and sometimes neglect of national policies and agendas according to specific local priorities.